2004
DOI: 10.1007/s00383-003-1115-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipid administration on liver apoptotic signals in a mouse model of total parenteral nutrition (TPN)

Abstract: Lipids are an important component of total parenteral nutrition (TPN), contributing the largest caloric load per volume of solution and providing essential fatty acids necessary for survival. However, lipids are known to be causative factors in oxidative stress, which are expressed via the Bcl-2 family of proteins and/or Fas-mediated apoptosis in several tissues. Interestingly, we have recently observed an increase in hepatocyte apoptosis with administration of TPN. To address the mechanism of this apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…By TUNEL staining, the PN-10 group exhibited significant increase in apoptosis index compared with other groups, as well as for the peroxidation marker-MDA content. The proportion of hepatocyte apoptosis was high (44.59 F 6.68) compared with the result of the Tazuke et al study (0.56 F 0.03) [11], which might be explained by the use of different animals at different times of life and different counting system as well. The difference between the PN-7 and PN-10 groups was obvious, which might infer an accumulative effect in the process of liver injury.…”
Section: Discussioncontrasting
confidence: 54%
“…By TUNEL staining, the PN-10 group exhibited significant increase in apoptosis index compared with other groups, as well as for the peroxidation marker-MDA content. The proportion of hepatocyte apoptosis was high (44.59 F 6.68) compared with the result of the Tazuke et al study (0.56 F 0.03) [11], which might be explained by the use of different animals at different times of life and different counting system as well. The difference between the PN-7 and PN-10 groups was obvious, which might infer an accumulative effect in the process of liver injury.…”
Section: Discussioncontrasting
confidence: 54%
“…An animal experiment demonstrated that TPN with lipid increased the expression of Fas and both the proapoptotic factor Bad and the antiapoptotic factor Bcl-xl. These changes may contribute to TPN-induced hepatocyte injury (apoptosis) or may suppress the ability of liver hepatocytes to regenerate [19].…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral nutrition-associated liver disease is characterized by a spectrum of fatty liver disease, inflammation, bile duct proliferation, fibrosis, and cirrhosis. Biochemically, the disease is in part because of TNF-α-mediated inflammation and FasL-mediated apoptosis in animal models [15,16]. In our initial studies, we hypothesized that the development of PNALD may be dependent on the type of fat administered (soybean oil-based vs fish oil-based) and that omega-3 fatty acids would prevent or reduce de novo lipogenesis and subsequent liver injury.…”
mentioning
confidence: 98%